2016
DOI: 10.1007/s00707-016-1756-5
|View full text |Cite
|
Sign up to set email alerts
|

Peak floor acceleration demand prediction based on response spectrum analysis of various sophistication

Abstract: This paper addresses the prediction of the median peak floor total acceleration (PFA) demand in spatial elastic structures subjected to seismic excitation. The prediction is based on various response spectrum methods of different degrees of sophistication. Beginning with a recently presented complete-quadraticcombination (CQC) rule for PFA demands, several approximations and simplifications concerning the correlation between modal contributions, peak factors, and cross-spectral moments are discussed, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Therefore, the peak factor, which represents the ratio between the peak acceleration and the mean square acceleration of a normal stationary random process [5,6], is unity, i.e. p i = 1.…”
Section: Approximate Peak Floor Acceleration Demand Prediction In Inementioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the peak factor, which represents the ratio between the peak acceleration and the mean square acceleration of a normal stationary random process [5,6], is unity, i.e. p i = 1.…”
Section: Approximate Peak Floor Acceleration Demand Prediction In Inementioning
confidence: 99%
“…Preliminary studies have shown that this relation can also be applied for structures with moderate hardening backbone curve. The modal peak factors of the higher (elastic) modes, p i , i > 1, and the peak factor of the response process, p r , can be estimated by the framework for elastic structures provided in [5,6], as preliminary studies have shown.…”
Section: Approximate Peak Floor Acceleration Demand Prediction In Inementioning
confidence: 99%
See 3 more Smart Citations